ANALISIS KEPUASAN NASABAH TERHADAP KUALITAS PELAYANAN PT. BANK RAKYAT INDONESIA (PERSERO) TBK UNIT SEMURUP DENGAN PENDEKATAN ANALISIS KORESPONDENSI - Prettya Recha; Syafriandi Syafriandi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Bank Rakyat Indonesia (BRI) is the oldest bank in Indonesia. BRI's vision is to become a leading commercial bank that always prioritizes customer satisfaction. For the sake of the realization of this vision, BRI's party must maximally provide services to customers. The problem in this research is there is a service quality gap given by BRI Semurup Unit. The purpose of this study is to know the characteristics of customers of BRI unit semrup and the trend of customer satisfaction on service quality of  BRI Unit Semurup . This research is adescriptive research. The type of data used in this study is the primary data. The sample in this research is BRI unit Semurup customer who is aged over 17 years old, owns ATM and has used the service of BRI Unit Semurup at least 3 times. Methods of data collection with questionnaire distribution. Data analysis technique used is correspondence analysis. The results of this study show that customers tend to be very satisfied with the honest attitude of the officers of BRI Units in serving customers and on the indicators of the neatness of the appearance of the Officer BRI Unit Semurup when serving the customers and on the cleanliness and comfort indicator and the room of  BRI Unit Semurup . customers tend to bedissatisfied with the awareness of BRI unit Semurup officers' awareness of customer complaints, and information indicator indicators specifically by BRI unit  Semurup officers regarding BRI's products and services that are responsive to the responsiveness dimensions of the officers in handling customer complaints. On the dimension of reliability is the indicator of the speed of BRI officer units in serving customers. On the dimensions of physical evidence is on the seating availability indicators for customers who wait for the queue number and on the indicator of ATM network of BRI Unit Semurup. Keyword :quality service BRI unit Semurup, satisfaction customer,   correspondence analysis.